Are Ireland's immigrants integrating into its labour market? - Alan Barrett; David Duffy (Institute for the Study of Labor (IZA), 2007)
Ireland has experienced a remarkable change in its migratory patterns in recent years and has moved from experiencing large-scale emigration to receiving significant inflows. In this paper, we use data from a nationally representative sample of immigrants and natives drawn in 2005 to assess the occupational attainment of immigrants in Ireland relative to natives. It is found that immigrants, on average, are less likely to be in high-level occupations controlling for factors such as age and education. When looked at by year of arrival, it appears as if immigrants who arrived more recently have lower occupational attainment relative to earlier arrivals, thereby suggesting a process of integration. However, a closer analysis shows that the observation of better occupational attainment for earlier arrivals can be explained by a change in the national origin mix of Ireland's immigrants, with immigrants from the New Member States of the European Union having the lowest occupational attainment. Within national groups there is generally no clear evidence of improved occupational attainment over time.
urn:nbn:de:101:1-2008032730
Keywords: 330; Einwanderung; Berufliche Integration; Migranten; Arbeitsmarkt; Irland